Physicochemical and Structural Properties of Resistant Starch Prepared from Tacca Tuber Starch using Autoclaving-Cooling and Acid Hydrolysis Treatments - Yonata, Diode; Triwitono, Priyanto; Arsanti Lestari, Lily; Pranoto, Yudi (Trends in Sciences, 2024)
Tacca tuber (Tacca leontopetaloides) is a neglected and underutilized plant species. Recently, tacca tuber has been studied as a food plant source of high-amylose starch, so it has the potential to be developed into resistant starch (RS), especially type-3 RS (RS3). RS3 can be prepared through the autoclave-cooling (AC) process, but the RS produced is not optimal. Further increase in RS can be obtained through hydrolysis of citric acid (AH). Until now, systematic knowledge about the preparation method and characterization of RS3 produced from tacca tuber starch through the AC-AH process remains unavailable. This study aims to determine the physicochemical properties and structure of RS3 from tacca tuber starch made through the AC-AH process. Tacca tubers were obtained from the Garut coast, Indonesia. They were first extracted to obtain starch and then processed using the AC process to make RS3. The acquired RS3 was hydrolyzed using AH at various concentrations and hydrolysis times. The results showed that all treatments did not affect the proximate composition, except for water content. Significant effects were observed on amylose and RS levels. The swelling power, solubility, water holding capacity, oil holding capacity and color profile of RS3 also significantly changed. The morphology of RS3 was deformed, accompanied by a change in its crystal structure to a combination of B and V types. This alteration was followed by an increase in the relative crystallinity and thermal profile, while the paste profile decreased significantly. In conclusion, all preparation methods affected the physicochemical properties and structure of RS3 from yam starch, except for the proximate composition. AC-AH treatment with 0.3 M citric acid for 4 h is recommended for preparing RS3 because it produces the highest RS content. The acquired RS3 has the potential to be applied in products that require good paste stability, and have health benefits. HIGHLIGHTS Tacca tuber is a neglected and underutilized plant species, a potential source of high amylose starch to be developed into resistant starch type-3 (RS3). Autoclaving-cooling (AC) and citric acid hydrolysis (AH) treatments produced 32.40 % RS3. RS3 has an irregular, rough and agglomerate morphological structure. The crystal structure of RS3 is a combination of types B and V, with a relative crystallinity of 24.38 - 45.94 %. AC-AH treatment with 0.3 M citric acid for 4 h is recommended in preparing RS3 because it results in the highest RS content. GRAPHICAL ABSTRACT